2017
DOI: 10.1002/14651858.cd009883.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin mimetics for patients with myelodysplastic syndromes

Abstract: Analysis 1.33. Comparison 1 Thrombopoietin mimetics versus placebo, Outcome 33 Serious adverse events -di erent types of additional agents..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Furthermore, bleeding events were defined as number of patients with bleeding, not adjusted for exposure per patient month, so there was non-significant. These results were consistent with previous meta-analysis that when adjusted, there was significantly RR of bleeding (35).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, bleeding events were defined as number of patients with bleeding, not adjusted for exposure per patient month, so there was non-significant. These results were consistent with previous meta-analysis that when adjusted, there was significantly RR of bleeding (35).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, this meta-analysis included less than 10 trials, so the significance of publication bias is limited. A meta-analysis involving 746 patients found no significant differences in mortality (RR: 0.97; 95% CI: 0.73-1.27) and progression to AML (RR: 1.02; 95% CI: 0.59-1.77, P = 0.03), but a lower risk of bleeding events (RR: 0.92; 95% CI: 0.86-0.99) in MDS treated with TPO-RAs (35), which were also consistent with the results of the present meta-analysis.…”
Section: Discussionmentioning
confidence: 90%
“…In a meta-analysis, Dodillet et al found that treatment with TPO-RA resulted in a lower number of MDS patients suffering from bleeding events. Although some studies have highlighted the potential risk of TPO-RA in accelerating leukemic progression or an increase of blasts in MDS patients, 28-30 more recent data from randomized controlled trials 31-33 and meta-analyses 34 , 35 did not seem to confirm this. Moreover, preclinical studies found that eltrombopag could inhibit leukemic cell growth in tissue culture and in animal models of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis further supports these conclusions, stating that no comparison between both agents have been performed, and further research is mandatory to answer the open question. 52 …”
Section: Discussionmentioning
confidence: 99%